PENGARUH NILAI TUKAR DOMESTIK PADA MASA COVID-19 TERHADAP PERTUMBUHAN PEREKONOMIAN DI INDONESIA - Muhammad Riski Anugerah Pratama; Andriansyah Putra; Azky Wafy Hasibuan (IDEI: Jurnal Ekonomi & Bisnis, 2022)
This study aimed to analyze the effect of the domestic exchange rate during the Covid- 19 period on economic growth in Indonesia. This research was qualitative in nature, obtained from books, journals, and other articles about the relationship between exchange rates during the  Covid-19  period  and  the  economy  at  the  same  time.  Data  retrieval  in  this  study  was secondary data which was generally in the form of evidence, either in the form of notes or reports  that  were  published  and  documented  as  well  as  published  and  unpublished.  The secondary data used in this study was Rupiah exchange rate data obtained from the official website of Bank Indonesia. The results of this research and analysis would show how the movement  of  the  domestic  exchange  rate  during  the  Covid-19  period  and  information  on Indonesia's economic growth taken from the official website of the Central Statistics Agency (BPS) which would later be obtained whether there was an influence of the exchange rate on economic growth in Indonesia and also how to control the exchange rate in the economy as a whole.  Penelitian ini bertujuan untuk menganalisis pengaruh nilai tukar domestik pada masa Covid-19 terhadap pertumbuhan perekonomian di Indonesia. Penelitian ini bersifat kualitatif yang diperoleh dari buku, jurnal, dan artikel lainnya tentang hubungan nilai tukar pada masa Covid-19 dengan perekonomian dalam waktu yang sama. Pengambilan data dalam penelitian ini adalah data sekunder yang umumnya berupa bukti, baik berupa catatan atau laporan yang dimuat  dan  didokumentasikan  serta  dipublikasikan  dan  yang  tidak  dipublikasikan.  Data sekunder yang digunakan dalam penelitian ini berupa data nilai tukar Rupiah yang diperoleh dari laman resmi Bank Indonesia. Hasil dari penelitian dan analisis ini akan menunjukkan bagaimana pergerakan nilai  tukar domestik  di  masa  Covid-19  dan informasi  pertumbuhan ekonomi Indonesia yang diambil dari laman resmi Badan Pusat Statistik (BPS) yang nantinya akan diperoleh apakah ada pengaruh dari nilai tukar tersebut pada pertumbuhan ekonomi di Indonesia  dan  juga  bagaimana  pengendalian  nilai  tukar  tersebut  pada  perekonomian  selu- ruhnya.